Pelaksanaan Peningkatan Kesadaran Hukum di Lapas Kelas II Bengkulu - Putra, Imansyah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Special Class Guidance Institution for Children (LPKA) Class II Bengkulu is one of the children’s correctional institutions in Indonesia which is tasked to provide guidance to correctional students. This rehabilitation is carried to improve the quality of childrens who are in conflict with law. One of the coaching that they can do is coaching in increasing legal awareness for children at LPKA Class II Bengkulu. By looking at the facts in LPKA Clas II Bengkulu, this researchs will focus on level of legal awareness among childrens in LPKA Class II Bengkulu, efforts, and obstacles in implemented it. This research uses descriptive qualitative method, research data was obtained in the field using an interview method with LPKA Class II Bengkulu. The result are the level of legal awareness among children in LPKA Class II Bengkulu is still low, for this reason LPKA trying to overcome this condition by socialization and coaching for assisted children, but several obstacles are felt when carryin these effort, that obstacles are lack of awareness, community support, stigma community, quality an d quantity of law enforcement officers, and that is no operational standards in coaching.